Experimental and numerical investigation of suddenly expanded flow at sonic mach number - Ambareen Khan; Parvathy Rajendran; Sher Afghan Khan; Mamdooh Alwetaishi; It Ee Lee (Scientific Reports)
Abstract The sudden expansion at the blunt base is a widespread phenomenon in the case of shells, rockets, and missiles. This study uses passive control in the form of ribs of various shapes and sizes in an abruptly expanded square cross-section duct at sonic Mach number. Three area ratios are examined in this study: 3.61, 5.76, and 7.84. In this study, passive control is employed at sonic Mach number in a suddenly expanded square cross-section duct. Three distinct rib sizes (6 mm, 8 mm, and 10 mm in diameter) at four locations inside the duct (1D, 2D, 3D, and 4D). The rib shapes considered for this study, rectangular, triangular, and semi-circular ribs, are investigated experimentally in the first stage. Experimental pressure data is used to compute base drag quantitatively. The outcomes of the simulation and the experiments agree reasonably well. The most efficient rib shape is a rectangular one with a diameter of 10 mm and an area ratio of 3.61. It raises the base pressure to almost three times that of the surrounding air. However, when the rib diameter is 6 mm, the control increases the base pressure, nearly equal to the ambient pressure. The outcomes of this study can be utilized to design an aerospace vehicle that meets the mission requirements. The passive control does not impact a higher area ratio despite the nozzle being under-expanded. The flow field inside the duct remains unchanged with and without control. Therefore, the passive control does not aggravate the duct’s flow field.